Sustainable development goals and the need for inclusive quality education for persons with special needs in open distance Learning in Nigeria (2020)
This paper discussed the Sustainable Development Goals as it relates to the assurance of inclusive and equitable quality education, and promoting life-long learning opportunity for persons with special needs, in the Open Distance Learning (ODL) system, within the context of the Nigerian society. Considering the myriads of problems facing the current practice of special education in Nigeria, it is reasonable to assume that the education of persons with special needs calls for reform and adoption of inclusive education, if in reality, the Federal Government is ready to promote quality and equitable inclusive education in line with the objective to eliminate discrimination, marginalisation and stereotype against persons with special needs in the country, so as to promote education for all, irrespective of diversity and disability. By shifting priorities and concentrating greater efforts and investment in inclusive education for children and adults with disabilities, there would be enriched quality of life and maximum utilisation of their potentials